Geoinformation Management of Infrastructure Energy Projects in Arctic - Yaroslav A. PETROV; Valery M. ABRAMOV; Evgeniy A. BAIKOV; Eugene P. ISTOMIN; Tatiana V. VEKSHINA; Vyacheslav G. BURLOV; Ekaterina M. KORINETS; Oleg I. SHEVCHUK; Mikhail B. SHILIN; Igor A. SIKAREV (Communications of International Proceedings, 2021)
Paper presented geoinformation management development results for decision support while large infrastructure energy projects within Industry 4.0 period under conditions of climate change and Covid-19. The study uses web-technologies and the methods of data bases constructing. As research result, it is recommended the using of Earth remote sensing data within geoinformation support systems to increase the efficiency and reliability of projects realization. As implementation tools, it is proposed the using of aggregate modular expert systems with geoinformation digital online platforms, as modules, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks. As study results, some examples of geoinformation support with remote sensing data while large infrastructure energy projects in Arctic are demonstrated. The presented in article research results have significant scientific novelty and can be useful for state environmental control bodies, public environmental organizations of the civil sector and private institutional stockholders. While research, platform https://www.researchgate.net/profile/Valery_Abramov2/ was used for preliminary discussion and data exchange.
Keywords: Geoinformation Management; Energy Projects; Arctic